2017
DOI: 10.3233/jad-161231
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Radiosynthesis, and Preliminary in vitro and in vivo Evaluation of the Fluorinated Ceramide Trafficking Inhibitor (HPA-12) for Brain Applications

Abstract: Ceramide levels are increased in blood and brain tissue of Alzheimer's disease (AD) patients. Since the ceramide transporter protein (CERT) is the only known protein able to mediate non-vesicular transfer of ceramide between organelle membranes, the modulation of CERT function may impact on ceramide accumulation. The competitive CERT inhibitor N-(3-hydroxy-1-hydroxymethyl-3-phenylpropyl) dodecanamide (HPA-12) interferes with ceramide trafficking. To understand the role of ceramide/CERT in AD, HPA-12 can be a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…9b), suggesting gradual degradation of the inhibitors in the cell culture. This is in agreement with a recent study showing in vivo degradation of fluorinated HPA-12 in mice 26 . The cell-associated levels of these compounds reached peaks during the initial 4 h, partially decreased, and then plateaued up to 72 h (Supplementary Fig.…”
Section: High-affinity Cert Inhibitors With No Ceramide-like Moietysupporting
confidence: 94%
See 2 more Smart Citations
“…9b), suggesting gradual degradation of the inhibitors in the cell culture. This is in agreement with a recent study showing in vivo degradation of fluorinated HPA-12 in mice 26 . The cell-associated levels of these compounds reached peaks during the initial 4 h, partially decreased, and then plateaued up to 72 h (Supplementary Fig.…”
Section: High-affinity Cert Inhibitors With No Ceramide-like Moietysupporting
confidence: 94%
“…The availability of LTP inhibitors remains very limited except for a few LTP types, including sterol or oxysterol transfer proteins [27][28][29][30] and CERT 13,14,17,19 . (1R, 3S)-HPA-12 and its closely related compounds have so far been the only potent inhibitors of CERT effective in living cells 13,14,17,26,31 . Iminosugar-based structures were recently shown to be another type of ceramidemimicking CERT inhibitor, although their effectiveness toward living cells remains unclear 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the pharmacokinetics of HPA-12was described,and it was proven that the compound reaches the brain intact (24). Here, we found that after 4 weeks,the treatment of HPA-12 increases Cer andAβ levels.…”
Section: Discussionmentioning
confidence: 52%
“…CERTs are found in at least two isoforms,which differ for the presence of a 26-amino acid serine-rich domain (23). CERTs are expressed in the central nervous system, and they are crucial in embryogenesis and brain development (23)(24)(25). When CERTs' activity is blocked pharmacologically or genetically, by compromising the START domain of the protein, SM production decreases signi cantly (26,27).…”
mentioning
confidence: 99%